POVERTY, ENVIRONMENT AND SUSTAINABLE DEVELOPMENT - Guamba, Jose Manuel Elija (International Journal of Research -GRANTHAALAYAH, 2017)
The article discusses factors that influence the preparation and responses in the general cycle of emergencies and disasters (environmental contexts, social, political, economic, cultural and institutional) integrating psychological, social and physical knowledge about sustainability, vulnerability and risks. The conflict between development, poverty, the environment and peace has become one of the biggest evidence of the human current difficulties. Mankind has not only of the achievements and benefits of development; but also, the undesirable effects produced by this, as social inequalities, poverty, environmental degradation and weakening of the sense of community, otherness and security. For Vieira (2005, p. 333) "harmonization of relationships that humans have with nature and the obstinate struggle by the pacification of relations between human beings constitute the two sides of the same coin." The idea of sustainable development has a chance to overcome the end envisioned. But there are those who preach the need for a paradigm shift in the concept. In today’s society it is the eminence of unsustainability is global economic, social or environmental. A "cultural mutation" is necessary for sustainable development if organize around the following key relationships: with nature, with time, between citizens, and with the authority of the State. Pol (2002, p. 296) warns that, you can understand why sustainability, has "... a strong load of change of individual and social behavior and therefore requires knowledge of social and psychosocial processes involved." Thus, sustainable development requires action that can be called generically of participatory management and environmental education (awareness and availability of resources that lead to the development of habits and skills), to achieve shared social values from the formulation of plans and programmes aimed at changing behaviors and eradication of poverty.